Comparison between the Use of Lecture and Workbook in Improving the Academic Performance of Students in Ecology - Dr. Violeta F. Collado, Dr.Rosita P. Abubo (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aimed to compare the effectiveness of lecture and workbook in improving the academic performance of students in ecology in Don Mariano Marcos Memorial State University, Philippines. This an action research that made use of actual scores and interventions to improve the academic performance of 44 students enrolled in Ecology. There were 22 students in the A group (lecture) and another 22 students in B group (workbook). The use of pure lecture was applied to group A (lecture) and workbook was utilized to group B. The frequency, percentage and average mean were utilized to compare the performance of both groups in the pre-test and post-test. T-test was used to determine the difference of students’ performance. Both groups, group A (lecture) and group B (workbook) performed poorly (59%) before the utilization of lecture to group A and workbook to group B as interventions. The average performance of group A (lecture) after the implementation of lecture as intervention was very good (89%) with 21.38% progress while group B (workbook) got (90%) equivalent to very good performance with 23.09% progress. Both groups have improved in their academic performance in ecology after the utilization of interventions but the use of workbook was more advantageous.